The Mediatization Effect of Tiktok and Smartphone Addiction: A New Role of Mediatization Effect Uncovered - Jin, Tong; Tan, Kim Hua; Nor, Nurul Lina Mohd; Alias, Jamsari; Mat, Norazila; Yunos, Nasruddin (Journal of Posthumanism, 2025)
In the new media era, users always rely on short video applications represented by TikTok, and the discussion on the essence and influence mechanism of this dependence phenomenon from the perspective of social communication and media theory is insufficient. Based on mediatization theory, it is necessary to further explore the mediatization effect of TikTok and its association with smartphone addiction. To validate the effectiveness of semi-structured interviews, this study conducted small-scale tests and preliminary thematic analysis on five Chinese college students. The research results verify that the performance of three key roles of mediatization effects proposed by Schulz (extension, substitution, and amalgamation) in TikTok can systematically affect users' smartphone use and generate addictive behaviors. The research results also found that there exists a new role of mediatization effect that can influence users’ online engagement behaviors and lead to smartphone addiction. As it is a small-scale test, the study has sample size and data saturation limitations. However, this study enriches the mediatization theory and provides practical inspiration for the intervention of smartphone addiction and the governance of short video platforms.